2005
DOI: 10.1074/jbc.m505537200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Apoptosis in HaCaT Keratinocytes via Differential Regulation of ERK Signaling Pathway by Flavonoids

Abstract: The exact molecular mechanisms underlying the cellular effects associated with various flavonoids have yet to be fully explained. In the present study, we have administered several flavonoids to human HaCaT keratinocytes and determined that 3,4-dihydroxy flavone (3,4-DHF) exerts a slight stimulatory effect on cell growth, although other flavonoids, including kaempferol, quercetin, and isorhamnetin, exhibited growth inhibitory properties. 3,4-DHF was found to exert an anti-apoptotic effect on etoposide-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 53 publications
5
78
1
Order By: Relevance
“…Previous studies have shown that etoposide-induced apoptosis of fibroblasts and keratinocytes is associated with an increase in Erk phosphorylation [51,52]. In fibroblasts, etoposide induced caspase activity, which was completely abrogated by inhibition of Erk activity [51,52]. In keeping with these reports, apoptosis of hepatocytes by Clostridium difficile toxin is accompanied by acute stimulation of Erk [53].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have shown that etoposide-induced apoptosis of fibroblasts and keratinocytes is associated with an increase in Erk phosphorylation [51,52]. In fibroblasts, etoposide induced caspase activity, which was completely abrogated by inhibition of Erk activity [51,52]. In keeping with these reports, apoptosis of hepatocytes by Clostridium difficile toxin is accompanied by acute stimulation of Erk [53].…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, etoposide alone resulted in acute phosphorylation of Erk at 30 min and occasionally weak and delayed Erk phosphorylation at 12-24 h ( Figure 7A). Previous studies have shown that etoposide-induced apoptosis of fibroblasts and keratinocytes is associated with an increase in Erk phosphorylation [51,52]. In fibroblasts, etoposide induced caspase activity, which was completely abrogated by inhibition of Erk activity [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ROS has been proposed as upstream event occurring during treatment with high (micro-molar) concentrations of trans-resveratrol [1,21], as well as with other polyphenols, including epigallocatechin-3-gallate [44,53), woodfordin I [35] and quercetin [33,64]. In our experimental system ROS burst occurs precociously (within the first hour) and the detrimental effects produced were confirmed by the increase in lipid peroxidation by-products, MDA and 4-HNE.…”
Section: Trans-resveratrol Induce a Selective Activation Of Jnk And Pmentioning
confidence: 75%
“…4A). TNF-α is pleiotropic pro-inflammatory cytokine that is produced by a wide range of activated cells (1,8). TNF-α stimulation results in the activation of IKK, which then phosphorylates IκBα at serine 32 and 36.…”
Section: Effect Of Flavonoids On Hek293 Cells Viabilitymentioning
confidence: 99%
“…These multiple biological activities have resulted in flavonoids gaining attention as potentially useful therapeutics for a variety of diseases such as cancer, cardiovascular diseases, autoimmune diseases and infectious diseases (7). However, despite the diverse beneficial biological and pharmacological effects of flavonoids, their use for the treatment of human diseases is not popular due to their high effective concentrations and poor absorptive effects and because their detailed molecular mechanisms have not yet been elucidated (7,8). Therefore, better understanding of their activities, action mechanisms and interaction with other compounds is necessary (7,9).…”
Section: Introductionmentioning
confidence: 99%